Evaluating The Impact of Online Product Review Credibility and Online Product Review Quality on Purchase Intention of Online Consumers - Josephine Diana S Campos; Jofrey R Campos (Applied Quantitative Analysis, 2024)
This study investigated the impacts of online product review credibility and quality on consumer purchase intentions for electronics, skincare, and home and kitchen products. Using Covariance-Based and Partial Least Squares Structural Equation Modeling (CB-SEM and PLS-SEM), it examines the causal links between review credibility, review quality, and consumer purchase intention. Conducted among 555 randomly selected online consumers from Metro Manila, Philippines, the study employed questionnaires with rating scales to gather data. Confirmatory factor analysis was utilized to assess model fit, reliability, and validity, while structural model and path analysis were applied to investigate the links between variables. The findings reveal that the structural model exhibits a moderate fit with the empirical data, demonstrating acceptable reliability and validity levels. Online review credibility was found to have a positive and direct impact on consumer purchase intention. Review quality was identified as a partial mediator in the relationship between review credibility and purchase intention, suggesting that it indirectly influences this dynamic. These implications suggest that e-commerce companies should emphasize the credibility of online product reviews by introducing guidelines to reduce the prevalence of misleading reviews. The accuracy and completeness of reviews, as determinants of review quality, should be prioritized to influence consumer decisions effectively. The study recommends that marketing strategies include incentives for customers to write honest and thorough reviews, thereby enhancing the overall quality of online product reviews. For future research, a qualitative or mixed-method approach is suggested to provide deeper insights, along with longitudinal studies to examine these effects over time.